Influence of tillage systems and of pulses and oilseeds succeeding rice (Oryza sativa) on chemical properties of soil - Pratibha, G; Hussain, M M; Pillai, K G; Satyanarayana, V (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during the winter season of 1989-90 and 1990-91 to study the effect of tillage practices on chemical properties of the soil. The tillage practices were: T1, no tillage; T2, ploughing twice with country plough; T3, ploughing twice with bullock-drawn mouldboard plough; T4, ploughing once with tractor-drawn mouldboard plough; T5, ploughing twice with cultivator; and T6, ploughing onceÂ  with tractor-drawn mouldboard plough followed by rotovator twice. The upland crops grown in sequence with rice (Olyza sativa L.) were blackgram (Phaseolus mungo L.), groundnut (Arachis hypogaea L.), castor (Ricinus communis L.) and sunflower (Helianlhus annuus L.). Land preparation in T6 arid T4 recorded higher values of organic carbon (0.46%) and available N, P and K content of soil during different stages of growth of these upland crops. Organic C (0.55%) and available N (291.4 kg/hal were high, whereas available P was low in soils at harvest, especially of groundnut, compared with those of other crops.